Thermal Conductivity of Some Sedimentary Rocks - Ab Rasid, Shahrul Aida (Universiti Teknologi Petronas, 2011)
Thermal conductivity or heat flow studies in geological studies currently become the significant interest of the oil and gas industry. These studies provided the initial estimation and indications on maturity of reservoir rocks thus provide better understanding of the reservoir. Thermal conductivity is not the same for any path flow. The ability to conduct heat depends on rock mineralogy and porosity. There are no specific values which can characterize thermal conductivity of a rock. Although several studies had been conducted on this particular subject, there is still lack of information on the variation of thermal conductivity value. The objective of this study is to evaluate and estimate the optimal number of samples required to characterize the thermal conductivity of the samples. The relationship between thermal conductivity and rock properties is also observed in this study. Several samples of argillaceous materials were selected from Batu Gajah area in Perak for this study. Experimental works for thermal conductivity are conducted using Needle Probe Method. All data obtained from the experiment are statistically analyzed using Statistical Package for Social Science (SPSS17) to reveal the variations of thermal conductivity. Samples properties were verified using X•Ray Diffraction, X•Ray Fluorescence, Scanning Electron Microscope, Fourier Transform Infrared Spectroscopy, Mercury Porosity meter, Total Organic Content and thin section. The fmding shows that thermal conductivity varies for different faces of each sample which are either parallel or perpendicular to the assumed bedding plane. The samples qualitative analysis suggests that each sample have different fabric in terms of particles size, particle orientation, mineralogy, porosity, TOC and relative permeability. Therefore, as a conclusion, thermal conductivity variation of some rocks is found to be affected by the heterogeneity of its fabric characteristics.